DEVELOPMENT OF PERSONAL DATA PROTECTION IN ARTIFICIAL INTELLIGENCE SYSTEMS FOR PROCESSING LEGAL NOTARY DOCUMENTS - Deri Sembiring; Gloria Gita Putri Ginting; Ayu Kurnia Sari (Journal of Information Technology, computer science and Electrical Engineering, 2026)
The development of Artificial Intelligence (AI) technology, particularly Natural Language Processing (NLP) and Optical Character Recognition (OCR), has brought significant efficiencies to legal document processing. In notarial practice, AI can be utilized for data extraction, automating deed drafting, verifying identity validity, and precisely and quickly identifying potential risky clauses. Conclusion Legal Alignment: By embedding Privacy by Design principles directly into the technical pipeline, the system bridges the gap between AI automation and legal compliance, satisfying both the strict confidentiality mandates of the Notary Position Law (UUJN) and the technical protection standards of the Personal Data Protection Law (UU PDP).